Analysis of sweating efficiency and its effects on the heat strain alleviation of clothed subjects. Issue 1 (13th January 2021) - Kuwabara, Kouhei; Hamada, Yasuhiro; Kubota, Hideki
Abstract: Sweating efficiency (SE) is essential for evaluating heat strain. The dripping of sweat off the skin surface of a nude subject occurs locally at an area where the secreted sweat exceeds the local evaporative capacity. However, in clothed subjects, "dripping" sweat is absorbed by clothing. In the present paper, the cooling efficiency of the sweating of a clothed subject is analyzed in relation to SE. First, typical patterns for the regional distribution of the sweat rate (SR) and the capacity of evaporation (CE) of a nude subject were introduced, and the dripping sweat rate was derived as a surplus of the SR over the CE; an equation of SE was derived from combinations of the two typical SR patterns and the uniform CE pattern. Then, the values of SE were calculated numerically, and the results were found to be approximately equal to those obtained experimentally by Alber–Wallerström & Holmér and theoretically from the equation of 1 − 0.5 wsw 2 used in ISO7933. Based on these results, the SE was improved by arranging the distribution of the CE by controlling air velocities over the body surface. Further, the improved SE was found to contribute to the heat strain alleviation of clothed subjects. Abstract : We analytically estimated the sweating efficiency of humans based on the surplus of the regional sweat rate over the regional capacity of evaporation. We improved the sweating efficiency by exposing the higher air velocity to the trunk area and proved its effect on heat strain alleviation of a clothed subject by predicting the mean skin temperature.